2015
DOI: 10.3109/17453674.2015.1055179
|View full text |Cite
|
Sign up to set email alerts
|

Knee arthroscopies: who gets them, what does the radiologist report, and what does the surgeon find?

Abstract: Background and purposeSeveral randomized controlled trials have not shown any added benefit of arthroscopy over placebo surgery or physiotherapy in middle-aged patients with knee symptoms without trauma. We studied the characteristics of the knee arthroscopies performed in southern Sweden.Patients and methodsFrom the orthopedic surgical records from 2007–2009 in the Skåne region of Sweden (with a population of 1.2 million), we retrieved ICD-10 diagnostic codes and selected all 4,096 arthroscopies that were dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
1
35
2
1
Order By: Relevance
“…This tear type is strongly associated with acute knee trauma and therefore more prevalent in younger sports-active patients 23. Our age-stratified analysis did not indicate any association between meniscal tears (at large) and mechanical symptoms among patients aged 18–40 years.…”
Section: Discussioncontrasting
confidence: 54%
“…This tear type is strongly associated with acute knee trauma and therefore more prevalent in younger sports-active patients 23. Our age-stratified analysis did not indicate any association between meniscal tears (at large) and mechanical symptoms among patients aged 18–40 years.…”
Section: Discussioncontrasting
confidence: 54%
“…2008, Bergkvist et al. 2016). Most of these patients have degenerative meniscal tears (Thorlund et al.…”
Section: Discussionmentioning
confidence: 99%
“…A recent registry-based study including information from plain radiographs, MRI, and arthroscopy found that about one-third of knee arthroscopies in Sweden were performed on patients with degenerative meniscal tears and/or osteoarthritis (Bergkvist et al. 2016). This is despite the fact of systematic reviews reporting no added benefit of surgery over that of placebo or additional effect of surgery in addition to exercise therapy for patients with early signs of knee osteoarthritis (OA) (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over half of these are performed to treat a meniscus tear in a degenerative knee 1. However, several recent randomised trials have shown that APM is not superior to conservative treatment or placebo treating meniscus tears associated with a degenerative knee 2…”
Section: Contextmentioning
confidence: 99%